Efficacy and safety of antibiotic agents in the treatment of rosacea: a systemic network meta-analysis - Xiao, Wenqin; Chen, Mengting; Wang, Ben; Huang, Yingxue; Zhao, Zhixiang; Deng, Zhili; Xie, Hongfu; Li, Ji; Tang, Yan (Frontiers in Pharmacology, 2023)
Background: Antibiotics are the backbone of rosacea management, especially for controlling inflammatory papules and pustules. We aim to evaluate the efficacy and safety of varied prescriptions and doses of antibiotics in treating rosacea by network meta-analysis. Methods: In this study, we compared all available randomized controlled trials (RCTs) studying systemic and topical antibiotics and placebo in rosacea therapy. We searched the databases including the Cochrane Central Register of Controlled Trials (CENTRAL), MEDLINE, Embase, Pubmed, Web of Science, and LILACS for published and unpublished RCTs on ClinicalTrials.gov before April, 2023. The primary outcome was the improvement of the Investigator's Global Assessment (IGA) scores, and the secondary outcomes consisted of the improvement of the Patient’s Global Assessment (PaGA) scores, Clinician’s Erythema Assessment (CEA) scores, as well as the adverse events (AEs). We used Bayesian random effects models for multiple treatment comparisons. Results: We identified 1703 results through these databases. Thirty-one randomized trials with 8226 patients were included. The heterogeneity and inconsistency between trials were low, so as a low risk of bias of all trials. Oral doxycycline 40mg, minocycline 100mg and minocycline 40mg, as well as topical ivermectin and metronidazole 0.75%, were effective in treating papules and pustules, namely decreasing IGA, in rosacea. Among which, minocycline 100mg ranked top in the efficacy. As for improving PaGA scores, topical ivermectin, metronidazole 1% and systemic oxytetracycline were effective, of which oxytetracycline works the best. Both doxycycline 40mg and metronidazole 0.75% presented no therapeutic effect for erythema. Considering the safety of the agents, systemic application of azithromycin and doxycycline 100mg significantly increase the risk of AEs. Conclusion: Our review suggests that a high dosage of systemic minocycline was the most effective in treating rosacea phenotypes with papules and pustules with a low risk of adverse events. However, there was no sufficient evidence-based data in exploring the influence of antibiotics on erythema. The phenotype of rosacea should be taken into consideration along with the benefit and safety when making the prescriptions.